Understanding the Impact of Natural Disaster in Micro, Small, and Medium Enterprises in Halal Food Sector - Sofyan, Syaakir; Arifin, Sirajul; Sofyan, A. Syathir; Syamsu, N.; Mansyur, Abdurrahman; Fauz, Ahmad; Waluya, Atep Hendang (UIN Raden Mas Said Surakarta, 2021)
Studies on the impact of disasters on Micro, Small and Medium Enterprises (MSMEs) in the halal food sector are often ignored by researchers and academics, even though these studies are needed to mitigate the risks from natural disasters. This study explores the impact of disasters on MSMEs, especially those engaged in the halal food sector. The research methodology used was phenomenology, with the data source being MSME actors in the halal food sector who were affected by the disaster in Palu City. The results of this study provide a conceptual framework for disaster impacts, which include direct and indirect impacts on physical assets, human resources, raw materials, production, sales, and capital. The relationship between the impact of the disaster and economic actors in the halal food sector breaks the supply chain in impacted and non-impacted areas. Therefore, the aim of this research is to provide information for business actors in Palu city to redesign a safer and more controlled business concept in the event of a natural disaster in the future.